AN ANALYSIS OF STUDENTS’ ERRORS IN WRITING COMPARATIVE AND SUPERLATIVE ADJECTIVE - Natalia Widya Pasca Tarigan (BIP: Jurnal Bahasa Indonesia Prima, 2021)
Abstract-This research was conducted to find out the impact of writing comparative and superlative adjective to analyze students’ errors in writing and to observe the students’ error in writing. The main purpose of the research is to observe if students get the errors in their writing comparative and superlative adjective. Qualitative research is used. The findings indicated that the error of misinformation 43.28%, error of misordering 22,11%, error of addition 18,07%, and error of omission 16,52%. It showed that students encounter problems and difficulties in writing comparative and superlative adjective. The conclusion is that educators should provide more effective ways in teaching comparative and superlative adjective so that the students can be better in using that in writing. Keywords : Student’s error, Writing Skill, Comparative and Superlative Adjective